Biocatalytic Synthesis of Flavor Ester "Pentyl Valerate" Using Candida rugosa Lipase Immobilized in Microemulsion Based Organogels: Effect of Parameters and Reusability. (1st July 2014) - Raghavendra, Tripti; Panchal, Nilam; Divecha, Jyoti; Shah, Amita; Madamwar, Datta
Abstract : Pentyl valerate was synthesized biocatalytically using Candida rugosa lipase (CRL) immobilized in microemulsion based organogels (MBGs). The optimum conditions were found to be pH 7.0, temperature of 37°C, ratio of concentration of water to surfactant (Wo) of 60, and the surfactant sodium bis-2-(ethylhexyl)sulfosuccinate (AOT) for MBG preparation. Although kinetic studies revealed that the enzyme in free form had high affinity towards substrates (K m = 23.2 mM for pentanol and 76.92 mM for valeric acid) whereas, after immobilization, the K m values increased considerably (74.07 mM for pentanol and 83.3 mM for valeric acid) resulting in a slower reaction rate, the maximum conversion was much higher in case of immobilized enzyme (~99%) as compared to free enzyme (~19%). Simultaneous effects of important parameters were studied using response surface methodology (RSM) conjugated with Box-Behnken design (BBD) with five variables (process parameters), namely, enzyme concentration, initial water content (Wo), solvent used for MBG preparation, substrate ratio and time, and response as the final product formation, that is, pentyl valerate (%). The MBGs were reused for 10 consecutive cycles for ester synthesis. Efficacy of AOT/isooctane as dehydrating agent for extracting excess water from MBGs was found to exert a positive effect on the esterification reaction.